Radar essentials a concise handbook for radar design and performance analysis - Curry, G. Richard (SciTech Pub., 2011)
Annotation When you need vital data fast, turn to Radar Essentials. This compact yet comprehensive reference has compiled the most used principles, data, tables, and equations that are used by radar and aerospace system designers on a daily basis. Experts and non-experts alike will find this to be their go-to source for recalling and understanding the fundamentals and employing them in design and performance analysis.KEY FEATURES- Discussion of principles, design, and operation including radar functions, types, frequencies, configurations and nomenclature.- Characteristics and capabilities of key subsystems including antennas, transmitters, receivers, T/R modules, and signal and data processing.- Radar performance evaluation techniques and data including radar cross section, signal-to-noise ratio, target detection, search, radar measurements, and tracking.- Discussion and data on the radar environment including atmospheric refraction and losses, rain attenuation, terrain, sea and rain clutter, terrain masking and multipath, ionospheric effects on radar performance, and electronic countermeasures.- Radar techniques including waveform design, moving-target indication (MTI), displaced phase-center arrays (DPCA), pulse Doppler operation, space-time adaptive processing (STAP), and target classification, discrimination and identification.
Keywords: Radar -- Handbooks, manuals, etc.; Radar -- Design and construction.; Radar -- Evaluation.; elektronické knihy; electronic books